Carbon-Based Materials as Catalyst Supports for Fischer–Tropsch Synthesis: A Review - Valero-Romero, María José; Rodríguez-Cano, Miguel Ángel; Palomo, José; Rodríguez-Mirasol, José; Cordero, Tomás (Frontiers in Materials, 2021)
The use of carbon-based materials as catalyst supports for Fischer-Tropsch synthesis (FTS) is thoroughly reviewed. The main factors to consider when using a carbonaceous catalyst support for FTS are first discussed. Then, the most relevant and recent literature on the topic from the last two decades is reviewed, classifying the different examples according to the carbon structure and shape. Some aspects such as the carbon textural properties, carbon support modification (functionalization and doping), catalyst preparation methods, metal particle size and location, catalyst stability and reducibility, the use of promoters and the catalyst performance for FTS are summarized and discussed. Finally, the main conclusions, advantages, limitations and perspectives of using carbon catalyst supports for FTS are outlined.